AN ANALYSIS OF THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 1 BANUHAMPU IN COMPREHENDING NARRATIVE TEXTS - Rahma Yani; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study is to find out the ability of the first year students of SMAN 1 Banuhampu in comprehending narrative texts. The population of this research were all of the first year students of SMAN 1 Banuhampu which consist of 238 students. There were 33 students who participated in this study. The instrument was a test adapted from authentic material and consists of 35 questions. The frame of the test covers 7 components: main idea, factual information, contextual meaning, reference, restatement, generic structure and language feature and had 5 questions for each component. Before the test was administered, the test was tried out to find out the difficulty level and the reliability of the test. To analyze the data, the raw scores and the level of ability of the students was calculated and identified by using the classification of ability level by Harris (1974). The result showed that the ability of the first year students of SMAN 1Banuhampu in comprehending narrative texts was at average to good level with mean score 72.12. Therefore, it can be concluded that most of the students were able to comprehend narrative text. However, the students are suggested to learn the seven components in comprehending narrative text that will help them in comprehending others reading texts.Key Words: Ability, Reading Comprehension, Narrative Texts